2011
DOI: 10.1007/s13312-011-0078-x
|View full text |Cite
|
Sign up to set email alerts
|

Holoprosencephaly: A guide to diagnosis and clinical management

Abstract: Context Holoprosencephaly affects 1 in 8,000 live births and is the most common structural anomaly of the developing forebrain, resulting in facial dysmorphism, neurologic impairment, and additional clinical sequelae. Given the increasing relative contribution of genetic diseases to perinatal morbidity and mortality in India, proper recognition and management of holoprosencephaly can improve care for a significant number of affected Indian children. Evidence Acquisition We used the PubMed database (search te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 44 publications
1
71
0
3
Order By: Relevance
“…8,9 This embryologic process is normally complete by the fifth week of gestation. The etiology of HPE is very heterogeneous and includes environmental and genetic causes.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 This embryologic process is normally complete by the fifth week of gestation. The etiology of HPE is very heterogeneous and includes environmental and genetic causes.…”
Section: Discussionmentioning
confidence: 99%
“…Trisomy 13 and other chromosomal abnormalities accounted for 50% of HPE, while mutations in Sonic Hedgehog (SHH) accounted for 17% of familial cases (Bullen et al, 2001). Improvements in our understanding and medical management have improved outcomes, particularly for less severe phenotypes (Chaudhary et al, 2011, Raam et al, 2011. This is evidenced by a hundred percent of lobar HPE patients surviving year one with an average age of 4.6 years-of-age at last follow up (Bullen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In a large series of 4,157,224 births, the same authors observed 370 infants with suspected holoprosencephaly (0,009%) stressing that isolated HPE was homogeneous among the 11 sampled countries, increasing from 0.5/10,000 births to 1/10,000 births between 1967 and 2000% [6]. The early embryonic occurrence may be even higher with prevalence of 1:250 in embryos [7] but may not be detected due to most fetuses aborting in early gestation [2]. In our small series of 4000 MRI explorations in children of different ages (from newborns to 15 years old) only three cases harboring HPE were diagnosed, accounting for almost 0.05%.…”
Section: Mini Reviewmentioning
confidence: 92%
“…Both genetic and teratogen factors are responsible for the development of HPE [1]. Rare in absolute terms, HPE is the most common brain abnormality and is seen in 1 per 8000-16,000 live births [2][3][4]. In an analysis of 21 HPE epidemiologic articles Orioli IM and Castilla EE [5] found that the pregnancy outcomes had relevant impact on the incident rate of HPE, being lower than 1 per 10,000 in live and stillbirth and between 40-50 per 10000 in aborted embryos.…”
Section: Mini Reviewmentioning
confidence: 99%